2008
DOI: 10.1007/s00228-008-0498-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism of CYP1A2 and the toxicity of leflunomide treatment in rheumatoid arthritis patients

Abstract: Our results suggest that the CYP1A2*1F allele may be associated with leflunomide toxicity in RA patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(42 citation statements)
references
References 22 publications
0
38
4
Order By: Relevance
“…The 16 However, no homozygotes for the CYP2C19*17 were found in our patient group. We have not analyzed other variant CYP2C19 alleles in our study.…”
Section: Resultscontrasting
confidence: 55%
“…The 16 However, no homozygotes for the CYP2C19*17 were found in our patient group. We have not analyzed other variant CYP2C19 alleles in our study.…”
Section: Resultscontrasting
confidence: 55%
“…In fact, the mitochondrial membrane potential of primary rat hepatocytes did show more sensitive to LEF than Figure S1). Many reports demonstrated that the polymorphism of several CYPs, such as CYP1A2 and CYP2C19, could affect the liver toxicity of LEF in patients with rheumatoid arthritis [24][25][26] , which could be indirect evidences that CYPs play a critical role in the detoxification of LEF in the body. Our studies with HRN mice are the first direct in vivo evidences that hepatic CYPs are involved in the clearance and toxicity of LEF.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found significant differences in CYP1A2 activity between ethnic groups (Swedes and Koreans), not related to environmental factors. 37 CYP1A2 polymorphisms could also be related to the toxicity of leflunomide in patients with rheumatoid arthritis 38 and seem to have a role in the efficacy of treatment of patients with antipsychotics, such as clozapine and olanzepine. 39 Several studies indicated implications of CYP1A2 polymorphisms in cancer susceptibility, namely for pancreatic cancer 40 and bladder cancer.…”
Section: Discussionmentioning
confidence: 99%